Peristiwa Pernikahan Dini dan Dampak Pola Pengasuhan Anak di Desa Baito dan Mekar Jaya Kecamatan Baito Kabupaten Konawe Selatan - Purwanti, Atni; Adi Jaya, Sarlan; Danial, Danial (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2025)
Early Marriage Events and the Impact of Childcare Patterns in Baito Village and Mekar Jaya Village in Baito District, South Konawe Regency. This study aims to find out and describe the reasons for early marriage in adolescents and the impact of childcare after early marriage in Baito Village and Mekar Jaya Village, Baito District, South Konawe Regency. This research uses the Levi-Straus structural theory, which is an ethnographic study of the ways in which the human intellect works. This theory is closely related to the human mindset in educating children. The results of the study can be concluded that 1) the reasons for early marriage are: a) weak parental control supervision, namely being allowed to date unsupervised so that the child goes overboard; b) promiscuity, resulting in easy fall into negative things such as free sex, drunkenness, and dropping out of school; c) the use of mobile phones, the opening of access to information from various parts of the world allows adolescents to easily receive and access various kinds of information including pornography; d) economic influence and cultural influence, the researcher saw that in Baito Village and Mekar Jaya Village, many teenagers who got married at an early age due to their parents' low economy so that by marrying their children, the burden of living costs was also reduced, besides that there were also parents who followed the hereditary culture, namely matching their children. 2) The impact of childcare after early marriage is the transfer of childcare roles from parents to grandmothers, who are prone to divorce because they cannot control their emotions and children receive less attention